2015
DOI: 10.1071/wf14143
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of repeated wildfire on long-unburned plant communities of the southern Appalachian Mountains

Abstract: The infrequent occurrence of large wildfires in the southern Appalachian Mountains over the last several decades has offered few opportunities to study their impacts. From 2000 to 2008, five wildfires burned a large portion of the area in and surrounding the Linville Gorge Wilderness in North Carolina. Areas were burned either once or twice. The response of acid cove and thermic oak plant communities (structure, cover, richness, diversity) was measured in 78 vegetation monitoring plots, established in 1992 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(43 reference statements)
1
10
1
Order By: Relevance
“…In the southern Appalachians, Hagan et al (2015) found that wildfires that included moderate to high fire severity resulted in the mortality of large overstory trees, leading to increased sapling stem density, and that twice-burned plots experienced the greatest increases in oak stem density. The authors attributed the increase in sapling density to the mortality of large overstory trees, vigorous resprouting, and the establishment of new individuals (Hagan et al 2015). Similarly, following a wildfire in a table mountain−pitch pine forest in the southern Appalachians, areas that burned with high fire severity experienced nearly complete stand mortality (Groeschl et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the southern Appalachians, Hagan et al (2015) found that wildfires that included moderate to high fire severity resulted in the mortality of large overstory trees, leading to increased sapling stem density, and that twice-burned plots experienced the greatest increases in oak stem density. The authors attributed the increase in sapling density to the mortality of large overstory trees, vigorous resprouting, and the establishment of new individuals (Hagan et al 2015). Similarly, following a wildfire in a table mountain−pitch pine forest in the southern Appalachians, areas that burned with high fire severity experienced nearly complete stand mortality (Groeschl et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kuddes-Fisher and Arthur (2002) found increased native herbaceous species richness following a single moderate-severity, late-winter prescribed fire on ridgetops within an oak−pine forest. In another oak−pine-dominated forest within the Appalachian region, total species richness increased following a single wildfire, in which upper slopes and ridges burned with high severity, and also increased in areas twice-burned by wildfire; however, the greatest increases in species richness occurred in areas burned twice (Hagan et al 2015).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Predictive models suggest that these wildfires would be very intense and have rapid spread rates (Waldrop et al 2010). If such fires were to occur, desirable levels of overstory mortality, herbaceous layer establishment, and oak regeneration could result (Hagan et al 2015). However, relying on a wildfire to meet restoration objectives is not recommended.…”
Section: Mechanical Treatment (M)mentioning
confidence: 99%
“…Increased evergreen understory may also have led to changes in leaf litter chemistry, decomposition rates, and other ecosystem properties (Monk et al 1985, Wurzburger and Hendrick 2007. Kalmia latifolia impacts on tree regeneration are less well studied, but it is generally the most common evergreen understory species on xeric sites in the southern Appalachians, and it also appears to suppress overstory tree regeneration (Moser et al 1996, Arthur et al 1998, Waldrop and Brose 1999, Abella et al 2003, Elliott et al 2009, Hagan et al 2015, Brose 2016.…”
Section: Introductionmentioning
confidence: 99%